Comparison of Formwork use in Building X Project in Surabaya City - Agriansyah, Eza; Suryo, Eko Andi; Arifi, Eva (Civil and Environmental Science Journal (CIVENSE), 2023)
The Value Engineering method is a method that analyzes the problems of a project through a systematic and organized approach by eliminating unnecessary costs without reducing the function, appearance, quality, and reliability of the project. The object x building, which has an estimated project value of IDR 42,812,329,371 in structural work. With the estimated value of the work costing a lot, it is, therefore, necessary to make efforts to streamline costs by using the value engineering method; this study aims to choose an alternative material for it. This research method uses a Pareto chart to find the highest work value. The results of this study indicate that the beam work is priced at IDR 15,088,457,899, floor plate work of IDR 12,530,471,281, column work of IDR 10,228,438,679. The results of the analysis of alternative structural calculations using semi-system formwork and full system formwork, which initially used conventional formwork, were simulated using alternative 1, namely semi-system formwork,k and by using alternative two full system formwork. The two alternatives are applied to column, beam and floor plate formwork. So, for this building, it is recommended to replace formwork because the conventional formwork used in this building incurs a large enough price, it is necessary to save on beam parts, and it is recommended to use full system formwork because the cost of beam formwork using full system formwork is IDR 134,950 per square meter. For the floor plate formwork, it is recommended to use a full floor plate formwork system because the cost per square meter is IDR 202,360. And for columns, it is recommended to use full system formwork because the cost of column formwork if using full system formwork is IDR 115,290. And from the use of all the full-system formwork for structural work, a total cost of IDR 40,312,992,291.32.